2010
DOI: 10.1135/cccc2010048
|View full text |Cite
|
Sign up to set email alerts
|

Glyoxyl analogs of indole phytoalexins: Synthesis and anticancer activity

Abstract: Glyoxyl analogs of indole phytoalexins brassinin, 1-methoxybrassinin, brassitin, 1-methoxybrassitin and 1-methoxybrassenin B were prepared, using (1H-indol-3-yl)-, (1-methoxyindol-3-yl)- and [1-(2,3,4,6-tetra-O-acetyl-β-D-glucopyranosyl)indol-3-yl]glyoxyl chlorides as starting compounds. Synthesized products were examined for their antiproliferative activity against human cancer cell lines Jurkat (T-cell acute lymphoblastic leukemia), MCF-7 (breast adenocarcinoma, estrogen receptor-positive), MDA-MB-231 (breas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 37 publications
0
8
0
Order By: Relevance
“…Glyoxylic analogs of natural phytoalexins, such as brassinin, brassitin, and some 1-methoxyindole phytoalexins, were synthesized. When comparing the antiproliferative activity of these derivatives to natural phytoalexins, it was shown that the most effective was an analog of glyoxylic 1-methoxybrassenin B (IC 50 3.3–66.1 μmol/L), which reduced the growth of cells in the most acute lymphoblastic leukemia line (CCRF-CEM) from a number of tested cancer cell lines (Jurkat, HeLa, MCF-7, MDA-MB231, A-549, CCRF-CEM) [87]. There are also several other studies on the anti-tumor effects of substances containing the indolyl glyoxylic group.…”
Section: Antiproliferative Effect Of Synthetic Derivatives Of Indomentioning
confidence: 99%
“…Glyoxylic analogs of natural phytoalexins, such as brassinin, brassitin, and some 1-methoxyindole phytoalexins, were synthesized. When comparing the antiproliferative activity of these derivatives to natural phytoalexins, it was shown that the most effective was an analog of glyoxylic 1-methoxybrassenin B (IC 50 3.3–66.1 μmol/L), which reduced the growth of cells in the most acute lymphoblastic leukemia line (CCRF-CEM) from a number of tested cancer cell lines (Jurkat, HeLa, MCF-7, MDA-MB231, A-549, CCRF-CEM) [87]. There are also several other studies on the anti-tumor effects of substances containing the indolyl glyoxylic group.…”
Section: Antiproliferative Effect Of Synthetic Derivatives Of Indomentioning
confidence: 99%
“…chemical synthesis and/or biosynthesis and bioactivity (Pedras et al, 2003b(Pedras et al, , 2007bPedras, 2008;Kutschy and Mezencev, 2008). More specific reviews on the antiproliferative and chemopreventive activity (Mezencev et al, 2003) and detoxification (Pedras and Ahiahonu, 2005) area.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, Izutani et al [6] described the ability of brassinin to inhibit cell growth in human colon cancer cells by arresting the cell cycle at the G 1 phase via increased expression of p21 and p27. In the last decade we have also documented the antiproliferative effects of brassinin or its derivatives in different cancer cells [25,26,27,28,29,30].…”
Section: Introductionmentioning
confidence: 99%